A Cross‐Sectional Comprehensive Assessment of the Profile and Burden of Non‐motor Symptoms in Relation to Motor Phenotype in the Nigeria Parkinson Disease Registry Cohort. Issue 8 (6th October 2021) - Ojo, Oluwadamilola O.; Wahab, Kolawole W.; Bello, Abiodun H.; Abubakar, Sani A.; Ekeh, Bertha C.; Otubogun, Folajimi M.; Iwuozo, Emmanuel U.; Farombi, Temitope H.; Adeniji, Olaleye; Ojini, Francis I.; Imarhiagbe, Frank A.; Nyandaiti, Yakub; et al.
ABSTRACT: Background: Data on non‐motor symptoms (NMS) in black Africans with Parkinson's disease (PD) are sparse. Objective: To describe the profile of NMS in the Nigeria PD Registry (NPDR) cohort and explore the relationship between NMS and PD motor phenotype. Methods: We conducted a cross‐sectional study of the frequency and burden of NMS, based on the non‐motor symptoms scale (NMSS) and the Chaudhuri method respectively in our cohort. Baseline demographics, disease characteristics (Hoehn and Yahr stage, MDS‐UPDRS total score and Part III motor score), motor phenotype (based on Stebbin et al's algorithm), and levodopa equivalent daily dose (LEDD) were documented. Results: Data are presented for 825 PD whose mean age at study was 63.7 ± 10.1 years, female sex—221 [26.8%] while median PD duration was 36 months. PD phenotypes included tremor‐dominant 466 (56.5%), postural instability and gait disorder (PIGD) 259 (31.4%), and indeterminate 100 (12.1%). 82.6% were on treatment (median LEDD of 500 mg/24 hours). 804 (97.5%) endorsed at least 1 NMS. The median NMSS score was 26.0 while subscores for urinary and sexual function domains were significantly higher in males ( P < 0.05). PIGD‐PD had more frequent NMS and higher frequency of severe/very severe NMSS burden ( P = 0.000 for both). Nocturia and fatigue were the most prevalent NMS overall and across motor subtypes. PIGD phenotype and total UPDRS scores were the independent determinants of NMSS scores ( P = 0.000). Conclusion: The profile and burden of NMS, and association with motor subtype in our black African cohort is largely similar to descriptions from other populations.